El Derecho Prehispánico en el Derecho Indiano: Causa criminal en la Nueva España por acciones indecentes y sublevación indígena - López Ledesma, Adriana (Cuadernos de Historia del Derecho, 2007)
Study of a lawsuit filed to two natives from the town of San Miguel de Mesquitic, jurisdiction of the Greater Mayorship of San Luis Potosí in the Nueva España. They were sued for irreverent behaviour through the use of insolent words and dishonest behaviour against the Christian religion. From there on, the exercise of the jurisdictional function unfolds, opposing the ordinary and the ecclesiastical judges, as well as the indigenous municipal authority - the “Republica de Indios”- both politically and procedurally. It all breaks in a political-legal ecclesiastical interaction that opposes jurisdictions, political powers, antagonistic cosmovisions, and ethnic plurality. The prohibitive total abrogation of the profession of indigenous faith is the distinguishing note of this case: the legality of Indian law prevails as the governing principle that concerts, balances and makes possible the daily coexistence of the two cultures.